Effect of two pre-freezing methods on quality of sexed semen in Ettawa Grade goat - Ondho, Y.S.; Udrayana, S.B. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The aim of this study was to determine the influence of pre-freezing different procedures to the quality of Ettawa Grade goat frozen semen-sexing. The research material was semen sexing consisted of 2 layers those were top layer and bottom layer. The quality of frozen semen sexing was observed by comparing the pre-freezing technique (factory standard operating procedure: FSOP) according to the  Artificial Insemination Center operating procedure (pre-freezing by placing the straw of semen for about 4 cm above liquid nitrogen for 9 minutes) with the modification procedure (MP), pre-freezing by placing the straw of semen 16 cm above liquid nitrogen for 9 minutes and then it was lowered to 4 cm above liquid nitrogen for 9 minutes during the pre-freezing phase. The parameters observed were motility, progressive motility, hyperactivation, and sperm linearity. Data were analyzed using Student's t-test.The results of this study indicated that the quality of sexed-semen in the standard operating procedures of frozen semen compared to the treatment of modifications to the top and bottom layers were motility at the top layer (46.06 ± 7.52% vs 55.6 ± 7.78%) and bottom layer (36.82 ± 6.49% vs. 41.47 ± 6.57%); progressive top layer (16.34 ± 4.27 vs. 32.83 ± 5.9%) and bottom layer 15.97 ± 2.72% vs. 19.79 ± 3.97%); hyperactivity in the top layer (0.81 ± 0.6% vs 4.09 ± 1.98%) and the bottom layer (0.71 ± 0.68% vs. 1.50 ± 1.05%); linearity consisted of linear and non-linear, the top layer (12.19 ± 2.94 vs. 20.52 ± 3.97%) and bottom layer (12.32 ± 2.63 vs 14.70 ± 2.6); while non-linear in top layer (0.14 ± 0.2 vs 0.68 ± 0.85%) and bottom layer (0.4 ± 0.13% vs 0.34 ± 0.4%). The conclusions in this study indicated that the quality of the frozen sexed-semen that has processed by pre-freezing modification technique was better than the frozen sexed-semen obtained from the Artificial Insemination Center Standard Operating procedure.